ON THE QUESTION OF THE RELATIONSHIP BETWEEN THE INSTITUTIONS OF “BLOOD FEUD” AND “TALION” (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the problem of the relationship between the institutions of “blood feud” and “talion”. The institution of blood feaud is a universal interdisciplinary institution of the law of the traditional society. Blood rushing, as a custom met at different times in different nations. The article reveals the principles of blood feud. According to the authors of the article, the principle of talion was the basis of blood revenge. Justifying this point of view, the authors note that the blood revenge could cause reciprocal blood revenge and initiate an endless relay race of murders, which could lead to the death of both hostile groups. Necessity was the emergence of some rules governing conflicts between teams. The result was the famous principle, which is known as the talion. In the end, the talion comes to replace the blood feud. It should be noted that the principle of talion is characteristic of almost all legal systems at the initial stage of their development. This principle was known to be the laws of Hammurabi, the laws of 12 tables, Jewish law, medieval German laws, etc.However, fundamental changes in the economic, social life of society, expressed in the division of labor, the development of trade, etc. led to the fact that the talion from an effective regulator of social life turned into its opposite, “into something that disorganizes, destroys society”. To overcome the talion, society introduces certain measures, the main purpose of which is to limit the scope of the norms of equal retribution, which ultimately led to the formation of two types of norms: state-legal and moral. Research and analysis of the institutions of blood feud and talion in the traditional nomadic society of the Kazakhs showed that despite the weakness of state power, she was interested in a peaceful resolution of the conflict.Key words: talion, blood feud, conflict, jurisdiction, Jewish law, medieval German law, revenge.